2018
DOI: 10.3390/cancers10110424
|View full text |Cite
|
Sign up to set email alerts
|

Population Based Testing for Primary Prevention: A Systematic Review

Abstract: The current clinical model for genetic testing is based on clinical-criteria/family-history (FH) and a pre-defined mutation probability threshold. It requires people to develop cancer before identifying unaffected individuals in the family to target prevention. This process is inefficient, resource intensive and misses >50% of individuals or mutation carriers at risk. Population genetic-testing can overcome these limitations. It is technically feasible to test populations on a large scale; genetic-testing cost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 82 publications
1
29
0
Order By: Relevance
“…An important role of BRCA1/2 testing is to identify high-risk variant carriers before they develop breast or ovarian cancer, so they may start cancer screening and preventive interventions to reduce cancer risk. However, evidence shows that current clinical genetic testing practice, which is primarily based on family history criteria and a predefined mutation probability threshold, is inefficient, resource-intensive, and misses >50% of individuals or mutation carriers at risk [1,14,30]. In a 2018 systematic review of population-based testing, the authors concluded that large scale general population-based screening can overcome these limitations as genetic-testing costs are falling and acceptability and awareness are increasing, yet there are few large-scale programs for unaffected women and a lack of evidence for their costs and consequences [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important role of BRCA1/2 testing is to identify high-risk variant carriers before they develop breast or ovarian cancer, so they may start cancer screening and preventive interventions to reduce cancer risk. However, evidence shows that current clinical genetic testing practice, which is primarily based on family history criteria and a predefined mutation probability threshold, is inefficient, resource-intensive, and misses >50% of individuals or mutation carriers at risk [1,14,30]. In a 2018 systematic review of population-based testing, the authors concluded that large scale general population-based screening can overcome these limitations as genetic-testing costs are falling and acceptability and awareness are increasing, yet there are few large-scale programs for unaffected women and a lack of evidence for their costs and consequences [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence shows that current clinical genetic testing practice, which is primarily based on family history criteria and a predefined mutation probability threshold, is inefficient, resource-intensive, and misses >50% of individuals or mutation carriers at risk [1,14,30]. In a 2018 systematic review of population-based testing, the authors concluded that large scale general population-based screening can overcome these limitations as genetic-testing costs are falling and acceptability and awareness are increasing, yet there are few large-scale programs for unaffected women and a lack of evidence for their costs and consequences [14]. Despite the positive trend in rates of BRCA1/2 testing, [31] the majority of at-risk women do not get a referral for genetic counseling and testing, and a large majority of BRCA1/2 variant carriers in the US have not been identified [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the most used population model for studying the feasibility and efficacy of the population-based BRCA testing is represented by Jewish population; however, implementation studies are needed for testing multiple cancer susceptibility genes in the general population [29]. Therefore, the current guidelines for genetic testing, based on clinical criteria and family history, could be replaced by new approaches able to detect the 50% more BRCA carriers than those identified by conventional criteria [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a mutation in BRCA1 or BRCA2 increases a woman's breast cancer risk by 6-7-fold; for ovarian cancer, the risk is upward of 30 or 10-fold over baseline, respectively [6][7][8][9][10][11][12][13][14]. Currently, most of genetic testing is carried out based on patient's personal history of cancer or high-risk family history [15]. Populationbased studies have been carried out in the Ashkenazi Jewish/Jewish populations [16][17][18], demonstrating potential feasibility and benefit.…”
Section: Introductionmentioning
confidence: 99%